Comparison of anterior colporrhaphy and vaginal mesh therapy for pelvic organ prolapse: a systematic review and meta-analysis - Mukhammad Arif Hadi Khoirudin; Nidia Nursafitri; Mauliya Sri Sukmawati Wahyudi; Muhammad Zainul Fikri; Dita Diana Parti; Wiwien Sugih Utami; Dian Eka Putri Harnandhari (Published by Universitas Gadjah Mada, 2025)
Pelvic organ prolapse (POP) is a common pelvic disorder among women. Although it is not life-threatening, POP represents significant health concern because it can cause urinary incontinence, decrease sexual function, and impair quality of life. This systematically review was conducted to compare the effectiveness and safety of anterior colporrhaphy with vaginal mesh therapy in the management of POP. The data sources were selected for their reputation in publishing high-quality research in urology and women’s health, including PubMed, Google Scholar, ScienceDirect, and the Cochrane Library, covering publications from 2014 to 2024. We included both randomized and non-randomized studies comparing anterior colporrhaphy with vaginal mesh therapy for stress urinary incontinence (SUI), ensuring a comprehensive review of the available evidence. Data were extracted on sample size, study location, surgical technique, patient satisfaction, reoperation rates, mesh erosion, pain, sexual function, operative time, length of hospital stay, and other complications. A total of 3,528 articles were collected. After removing 2,834 duplicates, 694 unique records remained. Following a quality assessment, six studies met the final inclusion criteria. Analysis of randomized controlled trials and cohort studies revealed no significant differences between the two procedures in terms of erosion rates, SUI incidence, reoperation rates, or patient satisfaction. These findings highlight the importance for urogynecologists to carefully consider patient identification, selection, comorbidities, and the choice of POP repair procedure.